2018
DOI: 10.18699/vj18.339
|View full text |Cite
|
Sign up to set email alerts
|

Using the Methods of Systems Biology for Predicting Perspective Target Genes to Select C3 and C4 Cereals for Oxidative Stress Resistance

Abstract: Reactive oxygen species (ROS) are some of the most damaging factors for living systems. Cells produce ROS during normal metabolism reactions, but ROS production increases under stressful conditions. Improving the antioxidant system in cultivated plants will increase their tolerance to abiotic stresses, such as salinity, drought and cold. However, the biochemical components of the system are redundant, for each reaction is catalyzed by a series of enzymes encoded by different genes. Choosing the most perspectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 30 publications
(37 reference statements)
0
9
0
Order By: Relevance
“…The stress response gene networks also change in the process of evolution; therefore, analysis of the systems of interacting genes, taking into account evolutionary patterns and expression data, allows the identification of features of the organization of response systems to stress factors and their most significant components promising for gene prioritization [16][17][18][19]. One promising approach in this regard is phylostratigraphic analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The stress response gene networks also change in the process of evolution; therefore, analysis of the systems of interacting genes, taking into account evolutionary patterns and expression data, allows the identification of features of the organization of response systems to stress factors and their most significant components promising for gene prioritization [16][17][18][19]. One promising approach in this regard is phylostratigraphic analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The catalytic efficiency (Kcat/Km) of the plant GPX is similar to other peroxidases (10 3 –10 6 M − 1 s − 1 ), but lower than that of APXs, CATs and human GPX (10 7 –10 8 M − 1 s − 1 ) ( Bela et al, 2015 ). Even though the role of GPX in the utilization of peroxide for plants is ambiguous in comparison with animals (due to presence of advanced ascorbate system in the cell), nevertheless, it has a similar number of paralogs as APX in plants, and many copies are highly conservative protein structure Doroshkov & Bobrovskikh (2018) . The term “glutathione peroxidase” itself is inaccurate for this enzyme since it has been shown that the enzyme is the 5th group of thioredoxin-dependent thiol peroxidases ( Navrot et al, 2006 ) and uses thioredoxins as a substrate, and not glutathione.…”
Section: Survey Methodologymentioning
confidence: 99%
“…In the AOS, there are individual enzyme-coding genes that have high importance for the functioning system in general, especially in stress conditions. Doroshkov & Bobrovskikh (2018) found the relationship between the evolutionary features of antioxidant enzymes and their expression levels for predicting prospective targets for selection across cereals. The authors identified groups of highly conserved genes with a high level of mRNA expression and a group of less conservative with a low-level expression.…”
Section: Survey Methodologymentioning
confidence: 99%
“…The catalytic efficiency (Kcat/Km) of the plant GPX is similar to other peroxidases (103-106 M −1 s −1 ), but lower than that of APXs, CATs and human GPX (107-108 M −1 s −1 ) (Bela et al, 2015). Even though the role of GPX in the utilization of peroxide for plants is ambiguous in comparison with animals (due to presence of advanced ascorbate system in the cell), nevertheless, it has a similar number of paralogs as APX in plants, and many copies are highly conservative protein structure Doroshkov and Bobrovskikh (2018). The term "glutathione peroxidase" itself is inaccurate for this enzyme since it has been shown that the enzyme is the 5th group of thioredoxin-dependent thiol peroxidases (Navrot et al, 2006) and uses thioredoxins as a substrate, and not glutathione.…”
Section: Main Features Of the Antioxidant System Componentsmentioning
confidence: 96%
“…In the AOS, there are individual enzyme-coding genes that have high importance for the functioning system in general, especially in stress conditions. Doroshkov and Bobrovskikh (2018) found the…”
Section: Stress-response Of the Antioxidant System Componentsmentioning
confidence: 99%